Bone Metastases from Prostate Cancer : Biology, Diagnosis and Management - Bertoldo, Francesco; Boccardo, Francesco; Bombardieri, Emilio; Evangelista, Laura; Valdagni, Riccardo (Springer International Publishing : Imprint: Springer, 2017)
This book presents up-to-date information on one of the hottest topics in prostate cancer, namely bone metastases. The most recent developments with respect to biology, pathology, diagnosis, and treatment are described, providing readers with an excellent understanding of the mechanisms of metastasis formation, the characteristics of metastases, their aggressiveness, and prognostic factors for treatment response. The coverage includes discussion of all of the best available options (laboratory, radiology, and nuclear medicine) for achieving early diagnosis and both established and novel therapeutic approaches. Detailed information is provided on hormonal manipulations, bone-targeted agents, vaccines, taxanes, and other treatments that are enriching the therapeutic armamentarium. The editors can be considered leaders in the field, with great experience in diagnostic and clinical oncology and research, and the authors are experts in diverse specialties. This ensures a multidisciplinary approach, mirroring the current situation in which treatment in patients with bone metastases is undertaken by a team of specialists and health professionals in a variety of fields.